2014
DOI: 10.1089/jwh.2013.4695
|View full text |Cite
|
Sign up to set email alerts
|

Promotora de Salud: Promoting Folic Acid Use Among Hispanic Women

Abstract: Background The U.S. Public Health Service recommends that all women in the United States capable of becoming pregnant consume 400 μg of folic acid daily to reduce their risk of having a pregnancy affected by a neural tube defect (NTD). However, disparities exist in the consumption of folic acid, with Hispanic women having lower rates of folic acid consumption than non-Hispanic white women. Methods A community-based feasibility study was designed to assess the utility of the promotora de salud model to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Further, the women who received the intervention were provided with a 90-day supply of multivitamin supplements. The cost of vitamins was mentioned in the pre-test as a barrier to vitamin use in both this study as well as in the earlier North Carolina-based pilot study, 7 and has been noted as a barrier in other studies as well. 23 The distribution of free supplements, then, provided a convenient way for these women to obtain supplements, while also removing the potential barrier of the cost of purchasing them.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Further, the women who received the intervention were provided with a 90-day supply of multivitamin supplements. The cost of vitamins was mentioned in the pre-test as a barrier to vitamin use in both this study as well as in the earlier North Carolina-based pilot study, 7 and has been noted as a barrier in other studies as well. 23 The distribution of free supplements, then, provided a convenient way for these women to obtain supplements, while also removing the potential barrier of the cost of purchasing them.…”
Section: Discussionmentioning
confidence: 52%
“…The provision of the multivitamins as part of the study design was done to be consistent with the earlier North Carolina-based pilot intervention project mentioned above. 7 Finally, the promotora informed participants that she would follow-up via telephone at two months to confirm their contact information, and at four months to conduct a final assessment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hispanic women are more likely to have a baby born with an NTD (Williams et al, 2015), and less likely to know about the benefits of folic acid in the prevention of NTDs (deRosset et al, 2014). Post-fortification studies found that Hispanic women were less likely to consume folic acid from either fortified foods or supplements (Hamner et al, 2013a; Hamner et al, 2011; Yang et al, 2007) and had lower overall median serum folate concentrations (Pfeiffer et al, 2012) than non-Hispanic white women, indicating that this group of Hispanic women might not be benefitting from the success of wheat and other cereal grain fortification as much as their non-Hispanic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Hispanic women report lower knowledge about the benefits of folic acid and lower folic acid consumption than women of other ethnic groups. 20,3032 Hispanic women also have higher rates of certain types of NTDs. 17,33–35 …”
Section: Introductionmentioning
confidence: 99%